Low-Load and High-Load Resistance Exercise Completed to Volitional Fatigue Induce Increases in Postexercise Metabolic Responses With More Prolonged Responses With the Low-Load Protocol - Grisebach, Daniel; Bornath, Derek P D; McCarthy, Seth F; Jarosz, Claudia; Hazell, Tom J (Journal of strength and conditioning research, 2024)
Grisebach, D, Bornath, DPD, McCarthy, SF, Jarosz, C, and Hazell, TJ. Low-load and high-load resistance exercise completed to volitional fatigue induce increases in post-exercise metabolic responses with more prolonged responses with the low-load protocol. J Strength Cond Res XX(X): 000-000, 2024-Comparisons of high-load with low-load resistance training (RT) exercise have demonstrated no differences in postexercise metabolism when volume is matched. This important limitation of matching or equating volume diminishes benefits of the low-load RT protocol. Therefore, the purpose of this study was to determine the effects of acute low-load high volume and high-load low volume RT protocols completed to volitional fatigue on postexercise metabolism. Eleven recreationally active resistance-trained male subjects (24 ± 2 years; BMI: 25.3 ± 1.5 kg·m-2) completed 3 experimental sessions: (a) no-exercise control (CTRL); (b) RT at 30% 1 repetition maximum (1RM; 30% 1RM); and (c) RT at 90% 1RM (90% 1RM) with oxygen consumption (V̇o2) measurements 2 hours postexercise. The RT sessions consisted of 3 sets of back squats, bench press, straight-leg deadlift, military press, and bent-over rows to volitional fatigue completed sequentially with 90 seconds of rest between sets and exercises. Changes were considered important if p < 0.100 with a ≥medium effect size. V̇o2 1 hour postexercise was elevated following 30% 1RM (25%; p = 0.003, d = 1.40) and 90% 1RM (14%; p = 0.010, d = 1.15) vs. CTRL and remained elevated 2 hours postexercise following 30% 1RM (16%; p = 0.010, d = 1.15) vs. CTRL. Total O2 consumed postexercise increased following 30% 1RM and 90% 1RM (∼17%; p < 0.044, d > 0.91) vs. CTRL. Fat oxidation was elevated 1 hour postexercise following 30% 1RM and 90% 1RM (∼155%; p < 0.001, d > 2.97) and remained elevated 2 hours postexercise following 30% 1RM compared with CTRL and 90% 1RM (∼69%; p < 0.030, d > 1.03). These data demonstrate beneficial changes to postexercise metabolism following high- and low-load RT sessions, with more prolonged effects following the low-load RT protocol completed to volitional fatigue.